2019
DOI: 10.15244/pjoes/90788
|View full text |Cite
|
Sign up to set email alerts
|

Macro and Structural Effects of Carbon Tax in China Based on the ECGE Model

Abstract: Rapid economic development has brought great pressure to China. Carbon tax could be an ideal economic tool to cope with the environmental pressure. The implementation of carbon tax will exert an influence on the national and sectoral economies as well as reduction. However, few researchers have focused on the carbon tax effect at the sectoral level. Based on SAM 2012, this study develops an ECGE model consisting of the environment module. Then the macro and structural effects of carbon tax are simulated at tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…These results are similar to previous studies (e.g. Zhou et al, 2022;Meng et al, 2013;Cao et al, 2021;Wu et al, 2019;Li and Su, 2017)…”
Section: Data and Scenariossupporting
confidence: 93%
See 4 more Smart Citations
“…These results are similar to previous studies (e.g. Zhou et al, 2022;Meng et al, 2013;Cao et al, 2021;Wu et al, 2019;Li and Su, 2017)…”
Section: Data and Scenariossupporting
confidence: 93%
“…In China, Cao et al (2021) compared carbon emission reduction due to the carbon tax among models and found that carbon emission mitigation was shown in all cases. Wu et al (2019) analyze the effects of carbon taxes ranging from 10 to 100 yuan/tCO 2 (around $1.6 to $15.7/tCO 2 ) imposed on the use of fossil energy in China by employing a CGE model and found that a carbon tax rate of 70 yuan/tCO 2 (around $11/tCO 2 ) could lead to the Chinese reduction target achievement in 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations